2023
DOI: 10.1039/d3nj02347h
|View full text |Cite
|
Sign up to set email alerts
|

Construction of a AgBr–Ag2MoO4 heterojunction and its photocatalytic sterilization activity

Abstract: AgBr-Ag2MoO4 heterojunction with high inactivation for E. coli under visible light illumination were constructed. The crystal structure, morphology, elemental composition, optical properties were characterized by TEM, SEM, XRD, XPS and...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 51 publications
0
1
0
Order By: Relevance
“…[4][5][6] In particular, nanocatalytic bacteriostatic materials have received widespread attention for the specific bactericidal properties due to the bacterial microenvironmental response properties. [7][8][9] In bacterial infection microenvironments (IME), transition metal nanomaterials with Fenton-like catalytic activity can convert endogenous H 2 O 2 into highly toxic reactive oxygen species (ROS) to destroy tumor cells or bacteria. [10][11][12] For instance, Junchuan Zhang et al reported that CuFe 2 O 4 triggered Fenton-like reactions in IME and exhibited notable antibacterial performance.…”
Section: Introductionmentioning
confidence: 99%
“…[4][5][6] In particular, nanocatalytic bacteriostatic materials have received widespread attention for the specific bactericidal properties due to the bacterial microenvironmental response properties. [7][8][9] In bacterial infection microenvironments (IME), transition metal nanomaterials with Fenton-like catalytic activity can convert endogenous H 2 O 2 into highly toxic reactive oxygen species (ROS) to destroy tumor cells or bacteria. [10][11][12] For instance, Junchuan Zhang et al reported that CuFe 2 O 4 triggered Fenton-like reactions in IME and exhibited notable antibacterial performance.…”
Section: Introductionmentioning
confidence: 99%